2016
DOI: 10.1016/j.jss.2015.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Trauma indices for prediction of acute respiratory distress syndrome

Abstract: Background A myriad of trauma indices have been validated to predict probability of trauma survival. We aimed to compare the performance of commonly used indices for the development of the Acute Respiratory Distress Syndrome (ARDS). Materials and Methods Historic, observational cohort study of 27,385 consecutive patients admitted to a statewide referral trauma center between July 11, 2003 and October 31, 2011. A validated algorithm was adapted to identify patients with ARDS. Each trauma index was evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The 1.8% incidence of ARDS among pediatric ICU patients is lower than the ARDS incidence among adults with traumatic injuries. 35,7,1011 This is consistent with previous findings that children have lower incidence of ARDS from all etiologies compared to adults. 13,26 While this may in part be due to differences in lung and chest wall development, pulmonary physiology, biomechanics, and mechanisms of injury, there may also be under-recognition of the problem.…”
Section: Discussionsupporting
confidence: 92%
“…The 1.8% incidence of ARDS among pediatric ICU patients is lower than the ARDS incidence among adults with traumatic injuries. 35,7,1011 This is consistent with previous findings that children have lower incidence of ARDS from all etiologies compared to adults. 13,26 While this may in part be due to differences in lung and chest wall development, pulmonary physiology, biomechanics, and mechanisms of injury, there may also be under-recognition of the problem.…”
Section: Discussionsupporting
confidence: 92%
“…After adjusting for underlying risk of mortality, the adjusted RR for death associated with ARDS was 1.51 (95% CI 1.42-1.62). Median time to death was 8 days (IQR 3-15) among ARDS patients and 3 days (IQR 1-8) among patients without ARDS; time to death was shortest among patients ≤4 years for both ARDS (3 days, IQR 2-5) and non-ARDS cohorts (2 days, IQR 1-4) and longer with each advancing age group until age 65-79 (ARDS 10 days [4][5][6][7][8][9][10][11][12][13][14][15][16][17]; non-ARDS 4 days [2][3][4][5][6][7][8][9][10]).…”
Section: Ards Mortality Across Agesmentioning
confidence: 99%
“…Severe traumatic injury is a well-described trigger for ARDS, with 5-10% of adult trauma patients [1][2][3][4] and up to 19% of adult trauma patients requiring intensive care unit (ICU) care 5 developing ARDS. Most studies of injured adults with ARDS have found a mortality rate of 16-24%, 2,3,[6][7][8][9] with estimates as high as 35-45% in severely ill cohorts. 1,10 The epidemiology of ARDS in the pediatric trauma population is not well described; the only study to date found an incidence of 1.8% with 20.0% mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A challenge in studying post-traumatic ARDS is to distinguish the effect of ARDS on outcomes from the impact of the severity of the injury itself. While most adult studies have found that unadjusted mortality is higher among patients with ARDS than those without, [15][16][17][18][19][20][21] several have found no additional impact of ARDS on mortality after adjusting for confounding factors such as age, injury severity, and physiologic parameters on admission. 15,16 We therefore aimed to evaluate outcomes among pediatric patients with post-traumatic ARDS by estimating risk for all-cause hospital mortality after adjusting for underlying mortality risk, and assessing markers of morbidity among survivors including hospital resource utilization and need for ongoing post-discharge care.…”
Section: Introductionmentioning
confidence: 99%